A performance study of dual-hop transmissions with fixed gain relays. - Hasna, M.O (IEEE Transactions on wireless communications)
This letter presents a study on the end-to-end performance of dual-hop wireless communication systems equipped with nonregenerative fixed gain relays and operating over flat Rayleigh-fading channels. More specifically, it first derives generic closed-form expressions for the outage probability and the average probability of error when the relays have arbitrary fixed gains. It then proposes a specific fixed gain relay that benefits from the knowledge of the first hop's average fading power and compares its performance with previously proposed relay gains that in contrast require knowledge of the instantaneous channel state information of the first hop. Finally, the letter investigates the effect of the relay saturation on the performance of the systems under consideration. Numerical results show that nonregenerative systems with fixed gain relays have a comparable performance to nonregenerative systems with variable gain, more complex, relays. These results also show that relay saturation of these systems results in a minimal loss in performance.